Final answer:
The equation g(x) = f(x) simplifies to 0 = x^2 - 4x. Solving this quadratic equation provides the values of x where these functions intersect, but the concept of a 'last term' is not applicable here as we are not dealing with a sequence.
Step-by-step explanation:
To find the value of g(x) when it is equal to f(x), we have to set the function f(x) = x + 2 equal to g(x) = x^2 - 3x + 2 and solve for x. This involves creating an equation x + 2 = x^2 - 3x + 2, which simplifies to 0 = x^2 - 4x. Solving this quadratic equation, by factoring or other methods, gives the values of x where these two functions intersect. However, the question regarding finding the last term seems incomplete or potentially misstated because in solving for x, we end up with a quadratic equation rather than a sequence where 'last term' would be relevant.